Influence of gender on nerve conduction parameters of median and ulnar nerves in healthy individuals - Shaesta Samol; Mohsin Hui; Dharitri Parmar; R. Dixit (International Journal of Medical Research and Review, 2016)
Background & objectives: Nerve conduction studies are used to diagnose disorders of the peripheral nervous system. They are influenced by number of variables i.e. age, gender, height, temperature, fiber diameter, degree of myelination, inter nodal distance etc. This study was conducted to analyze the effect of gender on nerve conduction parameters of upper limb nerves.Materials & Methods: The study comprised of 50 males and 50 females between the age group of 18-25 years. Distal latency, amplitude and conduction velocity of Median and Ulnar nerve were recorded using standardized technique.Results: The mean distal latency of sensory Median and Ulnar nerve were found to be significantly greater in males (p<0.05), whereas mean sensory amplitude was found to be significantly higher in female subjects, but the conduction velocity did not show any statistically significant difference (p>0.05). Mean distal latency and amplitude of motor median and ulnar nerve was found higher in males than females whereas conduction velocity was found to be higher in females but the difference was statistically insignificant.Conclusion: Gender has definite and significant influence on various Nerve Conduction Parameters. Without adjustment for this factor, the sensitivity and specificity of NCS will decrease when using the same reference data in patients with different gender.